Electrochemical biosensor : amperometric – glucose sensor - Zubir, Nazira (2015)
Biosensors consist of a biocatalyst and a transducer. The biocatalyst may be a cell, tissue or immobilized enzyme. The transducers are mainly amperometric, potentiometric or optical. Biosensors are tiny devices which involve biochemical reactions for identifying target analytes. The breakthrough of the biosensor is the enzyme nanoparticle-based biosensors which can assist in maximizing the diagnostic biochips with sensitive, rapid, accurate and precise monitoring.